Intrauterine administration of autologous peripheral blood mononuclear cells regulates the endometrium estrogen and progesterone receptor expression: An RCT - Fattaneh Farifteh; Elham Fazeli; Seyedeh Zeinab Hosseini; Seyedeh Soheila Arefi; Ashraf Moini; Robabeh Taheripanah; Fatemeh Rouhollah; Mohammad Salehi; Ahmad Hosseini; Moncef Benkhalifa (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Background: Repeated implantation failure (RIF) affects 15% of women of reproductive age. There is a high endometrial expression of both estrogen receptors and progesterone receptors (PRs) during the window of implantation in women with RIF. Objective: To evaluate the effects of intrauterine administration of human peripheral blood mononuclear cells (PBMC) on estrogen receptor α (ERα) and PRs expression in the endometrium of women with RIF during the implantation window. Materials and Methods: This randomized clinical trial study was conducted on 22 women with RIF history from January 2018 to August 2019 in Erfan hospital, Tehran, Iran. Participantswere divided into 2 groups (PBMC-treated group [n = 11] and control group [n = 11]). Endometrial tissue samples were collected at the implantation window time, during the mid-secretory phase (luteinizing hormone surge +7 days) of each menstrual cycle. The quantitative real-time polymerase chain reaction technique was used to measure the mRNA levels of ERα and PRs isoforms (PR-A and PR-B) in endometrial tissues. Furthermore, the protein expression of ERα and PRs was investigated using immunohistochemical staining. Results: PBMC treatment significantly decreased the mRNA expression of endometrial ERα and PRs isoforms at the time of the implantation window (p < 0.001). Moreover, the endometrial ERα and PRs protein localization were significantly lower in PBMC-treated women compared with controls (p = 0.01, and p < 0.001 respectively). Conclusion: The intrauterine administration of PBMC decreased the endometrial ERα and PRs expression during the window of implantation in women with RIF. This local response to PBMC therapy could promote endometrial receptivity and embryo implantation.